Menjelajahi SCM di Dunia Game: Studi Kasus Growtopia - Muhamad Paturahman; Achmad Syamsudin; Gema Borneo Poetra; Nurlia Eka Damayanti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study explores the distribution mechanisms within the virtual world of the online multiplayer game Growtopia and investigates their relevance to real-world supply chain management (SCM) practices. Using a qualitative case study approach, data were collected through in-depth interviews and virtual observation of player activities. The research identifies how virtual economies, player-driven logistics, and peer-to-peer transactions in Growtopia replicate fundamental SCM processes, including sourcing, inventory management, distribution, and end-user satisfaction. Furthermore, the study reveals that certain digital strategies used in the game, such as automated vending systems and community-based trust networks can inspire innovative SCM practices in digital commerce. The findings highlight the potential of game-based simulations as tools for SCM learning, experimentation, and adaptation in dynamic, digital environments. Keywords : Virtual Supply Chain; Growtopia; Game-based Simulation; Distribution Strategy; Supply Chain Management; Digital Economy